2005
DOI: 10.1002/art.20968
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for functional decline in older adults with arthritis

Abstract: Objective. Functional limitation is a major factor in medical costs. This study was undertaken to evaluate the prevalence of functional limitation among adults with arthritis and the frequency of functional decline over 2 years, and to investigate factors amenable to public health intervention that predict functional decline.Methods. Longitudinal data (1998-2000) from a cohort of 5,715 adults ages 65 years or older with arthritis from a national probability sample were analyzed. Function was defined based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
149
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(161 citation statements)
references
References 43 publications
9
149
2
1
Order By: Relevance
“…Associations between activity limitations in knee and/or hip OA and ethnicity (11,34,35), multiplesite joint pain (36,37), morning stiffness (38), comorbidity count (5,39), BMI (8), impaired hip flexion (33), bodily pain (8), general health perception (6), and the pain coping strategy transformation (40) have been identified previously in established OA. Furthermore, the results of the present study confirm earlier observations that radiographic status is not closely associated with physical function in patients with knee or hip OA (41)(42)(43).…”
Section: Discussionmentioning
confidence: 74%
“…Associations between activity limitations in knee and/or hip OA and ethnicity (11,34,35), multiplesite joint pain (36,37), morning stiffness (38), comorbidity count (5,39), BMI (8), impaired hip flexion (33), bodily pain (8), general health perception (6), and the pain coping strategy transformation (40) have been identified previously in established OA. Furthermore, the results of the present study confirm earlier observations that radiographic status is not closely associated with physical function in patients with knee or hip OA (41)(42)(43).…”
Section: Discussionmentioning
confidence: 74%
“…Studies have shown that sociodemographic characteristics are linked to neighborhood safety [14][15][16] and to long-term functional outcomes. [23][24][25] Baseline health and functional status can also have an impact on the perception of safety 14,15 and long-term functional status. [23][24][25] Race/ethnicity was categorized by participants' response to two questions (1) "Do you consider yourself primarily white or Caucasian, black or African American, American Indian or Asian or something else?"…”
Section: Methodsmentioning
confidence: 99%
“…Regression analyses were not performed individually in patients with ReA due to small numbers. Potential confounders for multivariate analyses for predicting health care utilization were chosen based on reports in other medical conditions [17][18][19]: (i) demographics: age (in years), gender (male/female), race (white vs other), education level (<8 grade, 8-11 grade, high school graduate or college and beyond), employment status (employed, unemployed, retired, unknown), marital status (married, not married); (ii) comorbidity: sum of comorbidities including asthma/COPD, depression, diabetes, hypertension or heart disease (comorbidity scale ranging from 0 to 5); (iii) current smoking status (smoker vs non smoker; and (iv) ADL limitations, categorized as 'no': 0 ADLs, 'moderate': 1-2 ADLs; or 'severe limitations': !3 ADLs; similar to previous studies [14,20]. All analyses were performed using SPSS version 11.0.1 (Chicago, IL, USA).…”
Section: Analysesmentioning
confidence: 97%
“…The survey provided data regarding marital status, education level and functional status. Physical function was assessed querying limitations (no, some, unable) in six activities of daily living (ADLs: bathing, dressing, eating, transferring to and from chair, walking and using the toilet)-a validated measure [13], used very commonly in cohort studies [14,15].…”
Section: Data Sourcesmentioning
confidence: 99%